Pengaruh Kualitas Kerja, Ketepatan Waktu dan Kompetensi terhadap Kinerja Karyawan (Studi Kasus pada Karyawan Hani Konveksi di Temanggung) - Fauziyah, Putri Lulu; Rahayu, Sri; Nurmiyati, Nurmiyati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyse the influence of work quality, punctuality, and competence on employee performance at Hani Konveksi in Temanggung. The research is motivated by the importance of human resource management in improving productivity within garment businesses, which often face challenges related to work accuracy, delays in task completion, and limited technical competence in handling complex designs. Effective management of these factors is essential to maintain product quality and competitiveness in the industry. This study employs a quantitative approach with a causal associative design. The sample consisted of 30 employees selected using a saturated sampling technique, where all members of the population were included as respondents. Data were analysed using multiple linear regression with the assistance of SPSS version 25. Prior to hypothesis testing, validity and reliability tests were conducted to ensure the quality of the research instruments. Hypothesis testing was carried out through t-tests, F-tests, and analysis of the coefficient of determination. The results indicate that work quality and competence have a significant partial effect on employee performance. This finding suggests that improving work accuracy and enhancing employees’ technical skills can directly contribute to better performance outcomes. In contrast, punctuality does not have a significant partial effect on performance. However, simultaneously, work quality, punctuality, and competence significantly influence employee performance. The coefficient of determination of 74.9% shows that most variations in employee performance are explained by these three variables. Overall, improving work quality and competence is crucial for enhancing performance in garment businesses.